2019
DOI: 10.3390/ijerph16173142
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Cognitive Emotion Regulation Strategies on Problematic Smartphone Use: Comparison between Problematic and Non-Problematic Adolescent Users

Abstract: Prior work has suggested that individuals with deficits in emotion regulation skills are prone to compulsive behaviour and to following maladaptive coping strategies, such as smartphone overuse, to manage negative moods. Adolescence is a vulnerable developmental stage for deficits in emotion regulation, and these are linked to excessive smartphone use. The present study is the first to examine the links between the use of specific cognitive emotion regulation (CER) strategies and problematic smartphone use in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 50 publications
(84 reference statements)
2
41
0
5
Order By: Relevance
“…[3][4][5] Compared to people of other age groups, adolescents, may be more vulnerable to the negative effects of smartphone use because they lack the ability to manage impulsive behaviors. 6 This problem is not limited to South Korea, as demonstrated by reports that 41.9% of Spanish adolescents 7 and 21.3% of Chinese adolescents 8 exhibited problematic smartphone use.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5] Compared to people of other age groups, adolescents, may be more vulnerable to the negative effects of smartphone use because they lack the ability to manage impulsive behaviors. 6 This problem is not limited to South Korea, as demonstrated by reports that 41.9% of Spanish adolescents 7 and 21.3% of Chinese adolescents 8 exhibited problematic smartphone use.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial amount of research findings point to the fact that psychological well-being can be enhanced by the use of adaptive emotion regulation strategies (Extremera et al, 2019). According to those researchers, Garnefski and Kraaij (2007) posited that there are individual differences in the way different people self-monitor the effect of maladaptive emotions by using adaptive and maladaptive cognitive emotion regulation strategies.…”
Section: Introductionmentioning
confidence: 99%
“…They found that cognitive reappraisal, which can be both an effective and ineffective strategy for regulating emotional responses to negative events, was positively associated with heavier smartphone use, and heavy use of smartphones was associated with increased problematic use. Fu et al 13 and Extremera, Quintana-Orts [14] found similar results with an adolescent sample whereby emotion regulation difficulties were associated with greater problematic smartphone use. It may be that emotion regulation difficulties are associated with being more distressed and therefore an increase in reliance on smartphones for comfort, reassurance, or emotional distraction in lieu of more adaptive emotion management 37 .…”
Section: Emotion Regulation and Problematic Smartphone Usementioning
confidence: 65%
“…Two proposed dispositional mechanisms are emotion regulation difficulties and personality. A poor ability to regulate emotional responses to negative experiences appears to be associated with greater problematic smartphone use in adults 6,11,12 and adolescents [13][14][15] . Similarly, broad personality traits, particularly high neuroticism and low conscientiousness, have also been found to predict greater problematic smartphone use [16][17][18][19][20][21][22][23] .…”
Section: Introductionmentioning
confidence: 99%